Energy conservation of Electric Hybrid Rickshaw with PV support - Haque, Shadman Shabaab; Sabrina, Hoque; Sabnin, Sanam; Zahid, Shah Omer (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2013.